1983
DOI: 10.1128/iai.42.3.965-972.1983
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of influenza as an immunogen in pulmonary antigen-presenting cells

Abstract: Influenza antigens inoculated into the lung induce local immune responses. It has been proposed that this induction might be partly regulated by local antigen-presenting cells. The purpose of the current study was to inoculate heat-inactivated influenza virus into the tracheae of guinea pigs and determine the quantity of antigens that became cell-associated. Second, we determined how long antigen-presenting bronchoalveolar cells that had taken up virus in vivo retained their ability to specifically stimulate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It is also possible that alveolar lavage lymphocytes are activated to cluster with monocytes-macrophages and become infected based on recent in vivo exposure to alternate antigens. Animal model studies have suggested that influenza antigens can persist in alveoli for weeks [ 72 ] to months [ 73 ] after exposure, and a high frequency of influenza-specific lung memory cells can be detected months after exposure [ 74 ]. Recent studies demonstrated that influenza-specific lung-resident memory T cells are proliferative and polyfunctional [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that alveolar lavage lymphocytes are activated to cluster with monocytes-macrophages and become infected based on recent in vivo exposure to alternate antigens. Animal model studies have suggested that influenza antigens can persist in alveoli for weeks [ 72 ] to months [ 73 ] after exposure, and a high frequency of influenza-specific lung memory cells can be detected months after exposure [ 74 ]. Recent studies demonstrated that influenza-specific lung-resident memory T cells are proliferative and polyfunctional [ 71 ].…”
Section: Discussionmentioning
confidence: 99%